2015
DOI: 10.1002/2015je004849
|View full text |Cite
|
Sign up to set email alerts
|

Periodic variations of oxygen EUV dayglow in the upper atmosphere of Venus: Hisaki/EXCEED observations

Abstract: International audienceUsing the Extreme Ultraviolet Spectroscope for Exospheric Dynamics (EXCEED) aboard Hisaki and the Solar Extreme Ultraviolet Monitor on the Solar and Heliospheric Observatory, we investigate variations of the extreme ultraviolet (EUV) dayglow brightness for OII 83.4 nm, OI 130.4 nm, and OI 135.6 nm in the Venusian upper atmosphere observed in March–April (period 1), April–May (period 2), and June–July (period 3) in 2014. The result shows that characteristic periodicities exist in the daygl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The data were provided by EXCEED onboard the Earthorbiting satellite Hisaki, which has produced quasi-continuous extreme ultraviolet (EUV) spectral images of solar planetary exospheres since its launch in 2013 Masunaga et al 2015). The EXCEED/ Hisaki observes a preselected target that satisfies the criterion that its elongation angle from the Sun exceeds 90° for outer planets or 25° for Venus and Mercury.…”
Section: Instrumentationmentioning
confidence: 99%
“…The data were provided by EXCEED onboard the Earthorbiting satellite Hisaki, which has produced quasi-continuous extreme ultraviolet (EUV) spectral images of solar planetary exospheres since its launch in 2013 Masunaga et al 2015). The EXCEED/ Hisaki observes a preselected target that satisfies the criterion that its elongation angle from the Sun exceeds 90° for outer planets or 25° for Venus and Mercury.…”
Section: Instrumentationmentioning
confidence: 99%
“…The Hisaki satellite was launched in September 2013 and entered into the orbit with the altitude of 950-1150 km [Yoshikawa et al, 2014]. The main purposes of Hisaki/EXCEED are to investigate plasma dynamics in Jupiter's magnetosphere [Yoshikawa et al, 2010;Tsuchiya et al, 2010;Yoshioka et al, 2012] and interactions between the upper atmospheres of terrestrial planets (i.e., Venus and Mars) and the solar wind [e.g., Masunaga et al, 2015]. Because Hisaki is the space telescope dedicated for the solar system science and because Jupiter's magnetosphere is one of the major targets, we can perform long-term and continuous monitoring of IPT.…”
Section: Observationmentioning
confidence: 99%
“…Kouyama et al (2015) showed, using a linear model for the vertical propagation of planetary-scale waves in the cloud-level atmosphere (60-80 km), that Kelvin waves cannot reach >75 km while the vertical propagation of Rossby waves highly depends on the vertical profile of the mean zonal wind. Masunaga et al (2015Masunaga et al ( , 2017 analyzed variations of the oxygen atom (O) dayglow intensity of the Venusian thermosphere on both dawnside and duskside using spectroscopic data obtained by the Extreme Ultraviolet Spectroscope for Exospheric Dynamics (EXCEED) on board the Hisaki spacecraft (Yoshikawa et al, 2014). They detected a periodicity of~4 Earth days in the dayglow intensity exclusively on the dawnside and pointed out that planetary-scale waves might be responsible for the periodic variations, although the existence of planetary-scale waves at thermospheric heights was not confirmed.…”
Section: Introductionmentioning
confidence: 99%